Development of a SARS-CoV-2 Vaccine Candidate Using Plant-Based Manufacturing and a Tobacco Mosaic Virus-like Nano-Particle - Royal, Joshua M.; Simpson, Carrie A.; McCormick, Alison A.; Phillips, Amanda; Hume, Steve; Morton, Josh; Shepherd, John; Oh, Youngjun; Swope, Kelsi; DeBeauchamp, Jennifer L.; Webby, Richard J.; Cross, Robert W.; et al. (Vaccines (Basel), 2021)
Stable, effective, easy-to-manufacture vaccines are critical to stopping the COVID-19 pandemic resulting from the coronavirus SARS-CoV-2. We constructed a vaccine candidate CoV-RBD121-NP, which is comprised of the SARS-CoV-2 receptor-binding domain (RBD) of the spike glycoprotein (S) fused to a human IgG1 Fc domain (CoV-RBD121) and conjugated to a modified tobacco mosaic virus (TMV) nanoparticle. In vitro, CoV-RBD121 bound to the host virus receptor ACE2 and to the monoclonal antibody CR3022, a neutralizing antibody that blocks S binding to ACE2. The CoV-RBD121-NP vaccine candidate retained key SARS-CoV-2 spike protein epitopes, had consistent manufacturing release properties of safety, identity, and strength, and displayed stable potency when stored for 12 months at 2–8 °C or 22–28 °C. Immunogenicity studies revealed strong antibody responses in C57BL/6 mice with non-adjuvanted or adjuvanted (7909 CpG) formulations. The non-adjuvanted vaccine induced a balanced Th1/Th2 response and antibodies that recognized both the S1 domain and full S protein from SARS2-CoV-2, whereas the adjuvanted vaccine induced a Th1-biased response. Both adjuvanted and non-adjuvanted vaccines induced virus neutralizing titers as measured by three different assays. Collectively, these data showed the production of a stable candidate vaccine for COVID-19 through the association of the SARS-CoV-2 RBD with the TMV-like nanoparticle.